Analysing Party Preferences Using Google Trends - Mirko Seithe; Lena Calahorrano (Center for Economic Studies and ifo Institute (CESifo), 2014)
The formation of party preferences is a complex and not yet fully understood process based on a number of factors. This process, which is of great interest for both social and political science, is usually studied using questionnaire data which has proven to be a very reliable yet often costly and limited approach. Advances in technology and the rise of the internet as a primary information source for many people have created a new approach to keep track of people's interests. The major gateways to the internet's information are the so-called search engines, and Google, arguably the most commonly used search engine, allows scientists to tap the vast source of information generated by its users' search queries. In this paper we describe how this data source can be used to estimate the effect of different issues on party preferences using German voters and the German party system as an example. We find that using data provided by Google Trends can lead to a variety of interesting and occasionally counter-intuitive insights into peoples' party preferences.
Keywords: D72; 330; voting behaviour; issue ownership; search volume; Google Trends